Artificial Heterogeneous Interphase Layer with Boosted Ion Affinity and Diffusion for Na/K‐Metal Batteries. Issue 13 (20th February 2022) - Jiang, Yu; Yang, Yang; Ling, Fangxin; Lu, Gongxun; Huang, Fanyang; Tao, Xinyong; Wu, Shufan; Cheng, Xiaolong; Liu, Fanfan; Li, Dongjun; Yang, Hai; Yao, Yu; et al.
Abstract: Metallic Na (K) are considered a promising anode materials for Na‐metal and K‐metal batteries because of their high theoretical capacity, low electrode potential, and abundant resources. However, the uncontrolled growth of Na (K) dendrites severely damages the stability of the electrode/electrolyte interface, resulting in battery failure. Herein, a heterogeneous interface layer consisting of metal vanadium nanoparticles and sodium sulfide (potassium sulfide) is introduced on the surface of a Na (K) foil (i.e., Na2 S/V/Na or K2 S/V/K). Experimental studies and theoretical calculations indicate that a heterogeneous Na2 S/V (K2 S/V) protective layer can effectively improve Na (K)‐ion adsorption and diffusion kinetics, inhibiting the growth of Na (K) dendrites during Na (K) plating/stripping. Based on the novel design of the heterogeneous layer, the symmetric Na2 S/V/Na cell displays a long lifespan of over 1000 h in a carbonate‐based electrolyte, and the K2 S/V/K electrode can operate for over 1300 h at 0.5 mA cm –2 with a capacity of 0.5 mAh cm –2 . Moreover, the Na full cell (Na3 V2 (PO4 )3 ||Na2 S/V/Na) exhibits a high energy density of 375 Wh kg –1 and a high power density of 23.5 kW kg –1 . The achievements support the development of heterogeneous protective layers for other high‐energy‐density metal batteries. Abstract : Long‐life Na‐metal and K‐metal batteries are realized by development of a heterogeneous protective layer consisting of metal vanadium nanoparticles and Na2 S (K2 S) on the surface of Na (K) foil. Such layer possesses the advantages of excellent sodiophilicity/potassiophilicity, high Young's modulus, and high ionic conductivity, inhibiting the dendrite growth during the repeated Na (K) plating/stripping.